Optimization of a piezoelectric linear motor in terms of the contact parameters - Ko, HP; Kim, S; Kang, CY; Kim, HJ; Yoon, SJ (ELSEVIER SCIENCE SA, 2005)
The contact kinetics of piezoelectric linear motors determines the operational characteristics like speed and torque or transmitted mechanical power and efficiency. Piezoelectric linear motors are driven by tangential stress in the interface between tip of shaking beam and slider. A good contact between the tip and slider is necessary for a reliable analysis of the motor, which is needed for the optimization of its performance. The piezoelectric linear motor was fabricated and the characteristics of the motor were investigated by external conditions such as tip shape with different curvatures and contact force between the tip and the slider. It was found in this investigation that the optimal curvature of the tip and the contact force are curvature of I and 10, respectively, for the high actuating speed, and curvature of 1 and 40 N, respectively, for the high actuating force. Finally, tip shape has an influence on the characteristics of linear motor. (C) 2004 Published by Elsevier B.V.